Crosslinker Copolymerization for Property Control in Inverse Vulcanization. Issue 44 (8th July 2019) - Smith, Jessica A.; Green, Sarah J.; Petcher, Samuel; Parker, Douglas J.; Zhang, Bowen; Worthington, Max J. H.; Wu, Xiaofeng; Kelly, Catherine A.; Baker, Thomas; Gibson, Christopher T.; Campbell, Jonathan A.; Lewis, David A.; et al.
Abstract: Sulfur is an underused by‐product of the petrochemicals industry. Recent research into inverse vulcanization has shown how this excess sulfur can be transformed into functional polymers, by stabilization with organic crosslinkers. For these interesting new materials to realize their potential for applications, more understanding and control of their physical properties is needed. Here we report four new terpolymers prepared from sulfur and two distinct alkene monomers that can be predictively tuned in glass transition, molecular weight, solubility, mechanical properties, and color. Abstract : Strengthening, altering and controlling the properties of inverse vulcanized sulfur polymers is of great importance. Over 60 million tons of sulfur are produced in excess by the petrochemical industry, and the potential applications of sulfur polymers are widespread. We investigate the mechanical properties and create a library of sulfur terpolymers.